Effective Clinical Pathway Improves Interprofessional Collaboration and Reduces Antibiotics Prophylaxis Use in Orthopedic Surgery in Hospitals in Indonesia - Fauna Herawati; Adinda Dessi Irawati; Ella Viani; Nully Andaretha Sugianto; Nur Laili Rahmatin; Made Prita Artika; Sukmawati Eka Bima Sahputri; Setiasih; Kevin Kantono; Rika Yulia; Retnosari Andrajati; Diantha Soemantri (MDPI AG, 2022)
Clinical pathways can improve the quality of health services. The effectiveness and impact of implementing clinical pathways are controversial. The preparation of clinical pathways not only enacts therapeutic guidelines but requires mutual agreement in accordance with the roles, duties, and contributions of each profession in the team. This study aimed to investigate the perception of interprofessional collaboration practices and the impact of clinical pathway implementation on collaborative and Defined Daily Dose (DDD) prophylactic antibiotics per 100 bed-days in orthopedic surgery. The Collaborative Practice Assessment Tool (CPAT) questionnaire was used as a tool to measure healthcare' perceptions of collaborative practice. The clinical pathway (CP) in this study was adapted from existing CPs published by the Indonesian Orthopaedic Association (Perhimpunan Dokter Spesialis Orthopaedi dan Traumatologi Indonesia, PABOI) and was commended by local domestic surgeons and orthopedic bodies. We then compared post-implementation results with pre-implementation clinical pathway data using ANCOVA to explore our categorical data and its influence towards CPAT response. ANOVA was then employed for aggregated DDD per 100 bed-days to compare pre and post intervention. The results showed that the relationships among members were associated with the working length. Six to ten years of working had a significantly better relationship among members than those who have worked one to five years. Interestingly, pharmacists' leadership score was significantly lower than other professions. The clinical pathway implementation reduced barriers in team collaboration, improved team coordination and organization, and reduced third-generation cephalosporin use for prophylaxis in surgery (pre: 59 DDD per 100 bed-days; post: 28 DDD per 100 bed-days). This shows that the clinical pathway could benefit antibiotic stewardship in improving antibiotic prescription, therefore reducing the incidence of resistant bacteria.